Annual Report on Migration and International Protection Statistics for Ireland: 2009 - JOYCE, CORONA (Report prepared for the European Commission Directorate-General Home Affairs & published by the ESRI, 2011)
This report provides an analysis of statistics relating to migration and international protection in Ireland and is the seventh in the current series. It aims to describe statistical trends on migration, international protection, refusals, apprehensions, residence permits and returns for the year 2009 based on Eurostat data, and to facilitate comparisons and interpretations pertaining to migratory trends on the European level as well as in the international context.
PUBLISHED
Dublin
Keywords: Migration; Asylum; International protection; Ireland